Red Flags and Red Tape: The Making of a Labour Bureaucracy - Leier, Mark (James Mark) (University of Toronto Press, 1995)
Labour bureaucracy has long been a subject of interest to sociologists and industrial relations specialists, but it has rarely been examined by labour historians. In Red Flags and Red Tape Mark Leier aims to understand how and why bureaucracy came to dominate an organization that was established to promote greater democracy for the working class. The formative years of the Vancouver Trades and Labour Council, from 1889 to 1910, provide the basis for his study of the interplay between bureaucracy, class, and ideology. Leier sets himself three tasks: he examines the theoretical debates on the labour bureaucracy; he investigates the early history of the VTLC to show how and why bureaucratic structures evolve over time; and he looks at the ideology and personnel of the labour council to try to understand the complex relationship between bureaucrats on the left and right of the political spectrum. He describes the ideology of the bureaucrats (including their attitudes towards gender and race) and how it compares to that of the council's members, and observes that bureaucrats are defined by their power over a movement rather than by their ideology. Finally, since the VTLC was, at different times, dominated by labourists and socialists, Leier explores why different leaders held variant or antagonistic views. Leier concludes that the pressure of trade unionism and the class position of labour officials led to increased bureaucracy and conservatism, even among the socialists of the labour council, and as the Vancouver Trades and Labour Council matured, increased red tape isolated the officials from the membership. –Publisher's description
Keywords: History; Ideology; Labor Unions; Labour leaders; Labour union democracy; Labour union federations; Labour unions; Vancouver Trades and Labour Council (VTLC); Vancouver; British Columbia